3D-3C wake field measurement, reconstruction and spatial distribution of a Panamax Bulk using towed underwater 2D-3C SPIV. (December 2020) - Wu, Tie-cheng; Deng, Rui; Luo, Wan-zhen; Sun, Peng-nan; Dai, Sai-shuai; Li, Yu-long
Highlights: This study focused on the measurement, reconstruction and spatial distribution of the 3D-3C wake field around Panamax Bulk using PIV. The 3D-3C wake field was reconstructed using the wake field data of multiple 2D planes obtained by scanning PIV measurements. The reconstructed volumetric measurement area is a cuboid region of length × width × height = 300 mm × 320 mm × 280 mm. The measured 3D-3C wake data provide a better understanding of the behaviour of vortices and turbulent structures of the hull. The 3D-3C wake data provide an important flow field information for the adaptive wake design of propeller and hydrodynamic appendage. Abstract: In this paper, a Panamax Bulk Carrier with bulbous bow and U-shaped stern with a scale ratio of 1/45 is studied. Measurements and mechanistic studies are carried out for a three-dimensional three-component (3D-3C) wake field using a customized towed underwater two-dimensional stereoscopic particle image velocimetry (2D-3C SPIV) system. The 2D-3C wake field data with multiple planes is obtained from the scanned PIV measurements of multiple 2D planes, this data is used to reconstruct the 3D-3C wake field. The reconstructed volumetric measurement area is a cuboid region with a length of 300 mm, width of 320 mm and height of 280 mm. Next, the spatial distributions of dimensionless axial u / U, lateral v / U and vertical w / U velocities are studied in detail based on the reconstructed 3D-3C wake field. The velocity data is used to analyze the dimensionless velocity magnitude in Y - Z Plane S / U and dimensionless average kinetic energy. Finally, the spatial distribution of vortices in the wake field is characterized. The 3D-3C measurements reveal the behavior of vortices and turbulent structures in the hull. These findings are essential for the adaptive wake designing of the propeller and hydrodynamic appendage.